Dampak Penggunaan Media Sosial pada Mahasiswa yang Mengalami Depresi - Nadia Khairina; Ragil Wahyu Hernawati; Rahma Rasyida (Universitas Negeri Malang, 2024)
The term depression is not something new today. Depression is an emotional disorder characterized by an individual's reduced interest in something. One of the causes of depression is related to social media. This research aims to examine the role of social media use in students who have experienced depression. This research uses a qualitative approach with in-depth interview methods. The selection of research participants was carried out using a purposive sampling technique. The criteria for participants were 1) students at the State University of Malang, 2) who had a history of depression, and 3) who were willing to be interviewed based on the criteria obtained by two research subjects. The data analysis technique used is thematic data analysis. Thematic analysis is one way to analyze data to identify patterns or find themes through data that has been collected by researchers. The interview process was carried out with participant 1 and participant 2 on Wednesday, November 22 2023. The research results showed that 1) social media has an impact on depression and 2) There is no definite pattern of relationship between the intensity of social media use and depression.